(untitled) (Baghdad Science Journal, 2024)
There is substantial data supporting the importance of both endogenous and exogenous estrogen in maintaining reproductive health and preventing chronic disease, androgens in women’s health are rarely discussed. This is one of the first researches to investigate correlates of blood testosterone concentrations in women with osteopenia, in anticipation of the growing interest in the role of androgens in women’s health. A 65 volunteer women were enrolled in the current study, they were divided into two groups, 35 postmenopausal women with osteopenia were in the first group, and the second group contained 30 postmenopausal women without osteopenia as a control. Blood samples were collected from all participants and analyzed for testosterone level, also demographic data were collected. The results showed that women with osteopenia have significantly low levels of testosterone as compared to control, the correlation analysis using postmenopausal women with osteopenia as a model showed a significant reversed correlation between testosterone and T score. Cluster analysis results illustrated that T-Score, testosterone and, duration of the postmenopausal were organized in one cluster, which means the three variables were associated with each other in most of the studied cases. The second cluster included t-score, testosterone and, BMI. Whereas the age factor contributed to the third cluster. Testosterone levels were significantly associated with osteopenia, which could indicate the development of osteoporosis in post-menopause women. Testosterone results were organized in one cluster with T-score and, duration of the postmenopausal. So the three variables were associated with each other in most studied cases.